Influence of Antibiotic Susceptibility Testing on Antibiotic Choice in Hospital-Acquired and Ventilator-Associated Pneumonia. (October 2020) - Zappernick, Taissa; Christian, Robbie; Sims, Sharanie; Wilson, Brigid; Perez, Federico; Bonomo, Robert; Jump, Robin
Abstract : Background: The survival of patients with hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) is largely determined by the timely administration of effective antibiotic therapy. Guidelines for the treatment HAP and VAP recommend empiric treatment with broad-spectrum antibiotics and tailoring of antibiotic therapy once results of microbiological testing are available. Objective: We examined the influence of bacterial identification and antibiotic susceptibility testing on antibiotic therapy for patients with HAP or VAP. Methods: We used the US Veterans' Health Administration (VHA) database to identify a retrospective cohort of patients diagnosed with HAP or VAP between fiscal year 2015 and 2018. We further analyzed patients who were started on empiric antibiotic therapy, for whom microbiological test results from a respiratory sample were available within 7 days and who were alive within 48 hours of sample collection. We used the antibiotic spectrum index (ASI) to compare antibiotics prescribed the day before and the day after availability of bacterial identification and antibiotic susceptibility testing results. Results : We identified 4, 669 cases of HAP and VAP in 4, 555 VHA patients. The median time from respiratory sample receipt in the laboratory to final result of bacterial identification and antibiotic susceptibility testing was 2.22 days (IQR, 1.31–3.38 days). The most common pathogen was Staphylococcus aureus (n = 994), with methicillin resistance in 58% of those isolates tested. The next most common pathogen was Pseudomonas spp (n = 946 isolates). The susceptibility of antipseudomonal antibiotics, when tested, was as follows: 64% to carbapenems, 74% to cephalosporins, 75% to β-lactam/β-lactamase inhibitors, 69% to fluoroquinolones, and 95% to amikacin. Lactose-fermenting gram-negative bacteria (296 Escherichia coli and 360 Klebsiella pneumoniae ) were also common. Among the 3, 094 cases who received empiric antibiotic therapy, 607 (20%) had antibiotics stopped the day after antibiotic susceptibility results became available, 920 (30%) had a decrease in ASI, 1, 075 (35%) had no change in ASI, and 492 (16%) had an increase in ASI (Fig. 1). Among the 1, 098 patients who were not started on empiric antibiotic therapy, only 154 (14%) were started on antibiotic therapy the day after antibiotic susceptibility results became available. Conclusions: Changes in antibiotic therapy occurred in at least two-thirds of cases the day after bacterial identification and antibiotic susceptibility results became available. These results highlight how respiratory cultures can inform the treatment and improve antibiotic stewardship for patients with HAP/VAP. Funding: This study was supported by Accelerate Diagnostics. Disclosures: None